Identification of Factors Affecting Tacrolimus Trough Levels in Latin American Pediatric Liver Transplant Patients. Issue 9 (25th June 2019) - Riva, Natalia; Woillard, Jean‐Baptiste; Distefano, Maximiliano; Moragas, Matias; Dip, Marcelo; Halac, Esteban; Cáceres Guido, Paulo; Licciardone, Nieves; Mangano, Andrea; Bosaleh, Andrea; de Davila, María Teresa; Schaiquevich, Paula; et al.
Abstract : Tacrolimus is the cornerstone in pediatric liver transplant immunosuppression. Despite close monitoring, fluctuations in tacrolimus blood levels affect safety and efficacy of immunosuppressive treatments. Identifying the factors related to the variability in tacrolimus exposure may be helpful in tailoring the dose. The aim of the present study was to characterize the clinical, pharmacological, and genetic variables associated with systemic tacrolimus exposure in pediatric liver transplant patients. De novo transplant patients with a survival of more than 1 month were considered for inclusion and were genotyped for cytochrome P450 3A5 (CYP3A5). Peritransplant clinical factors and laboratory covariates were recorded retrospectively between 1 month and 2 years after transplant, including alanine aminotransferase (ALT), aspartate aminotransferase, hematocrit, and tacrolimus predose steady‐state blood concentrations collected 12 hours after tacrolimus dosing. A linear mixed effect (LME) model was used to assess the association of these factors and the log‐transformed tacrolimus dose‐normalized trough concentration (logC0/D) levels. Bootstrapping was used to internally validate the final model. External validation was performed in an independent group of patients who matched the original population. The developed LME model described that logC0/D increases with increases in time after transplant (β = 0.019, 95% confidence interval [CI], 0.010‐0.028) and ALT values (β = 0.00030, 95% CI, 0.00002‐0.00056), whereas logC0/D is significantly lower in graft CYP3A5 expressers compared with nonexpressers (β = −0.349, 95% CI, −0.631 to −0.062). In conclusion, donor CYP3A5 genotype, time after transplant, and ALT values are associated with tacrolimus disposition between 1 month and 2 years after transplant. A better understanding of tacrolimus exposure is essential to minimize the occurrence of an out‐of‐range therapeutic window that may lead to adverse drug reactions or acute rejection.